2021
DOI: 10.3390/su14010168
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Loneliness in Psychological and Behavioral Profile among High School Students in Spain

Abstract: Loneliness is a distressing feeling that can be a barrier to a student’s development and affect their mental health. This research aimed to analyse the effects of loneliness on psychological and behavioral factors among students aged 12–19 years in Spain. Loneliness, experiential avoidance, psychological inflexibility, physical activity, mobile phone use, and smoke habits were analysed in a sample of 110 men and 122 women assigned into two groups depending on their loneliness levels: higher loneliness group (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It is shown that the fact of having a higher capacity for information processing and action in these highly eliciting situations, where the psychophysiological stress response is very high, is what predicts the performance in these military contexts. In line with previous studies [ 68 , 69 ], it would be interesting to analyze how other conditions, such as the psychological profile of the subject, can affect this stress response and modulate the habituation response to stressors as high as those pilots and military are submitted to.…”
Section: Discussionmentioning
confidence: 73%
“…It is shown that the fact of having a higher capacity for information processing and action in these highly eliciting situations, where the psychophysiological stress response is very high, is what predicts the performance in these military contexts. In line with previous studies [ 68 , 69 ], it would be interesting to analyze how other conditions, such as the psychological profile of the subject, can affect this stress response and modulate the habituation response to stressors as high as those pilots and military are submitted to.…”
Section: Discussionmentioning
confidence: 73%
“…It would be interesting to analyze the role of other factors as physical activity [59], dental health [59,60], psychological profile, especially loneliness [23], and social relationships [61] in the risk perception of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological profile: Based on the Spanish version of the Big Five Inventory (alpha coefficient 0.73) [23], the reduced version of the Big Five personality traits of 44 items was used, consisting of: openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism. It is composed of 10 items that are answered using a 5-point Likert scale, where 1 means completely disagree and 5 means completely agree.…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge of dietary factors could be used by health institutions to implement multidisciplinary interventions to reduce bad sedentary habits among people. Additionally, economic status was not included in questionnaires and could be considered an important issue to consider in future research as previous authors highlighted [64,65], as well as other contextual and behaviours factors as nutritional, social, and psychological patterns that could modulate the contextual profile of population [66][67][68][69]. Thus, global interventions in population are crucial for acquiring the right knowledge, convictions, skills, and attitudes that help shape a pro-healthy lifestyle and reduce blood pressure levels in the future.…”
Section: Practical Applicationsmentioning
confidence: 99%